2015
DOI: 10.1016/j.nrl.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Validación de la versión española del test Addenbrooke's Cognitive Examination III para el diagnóstico de demencia

Abstract: The Spanish version of the ACE-III is a reliable and valid test for diagnosing dementia. Its diagnostic accuracy is high, especially in patients with a higher level of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 21 publications
7
36
0
8
Order By: Relevance
“…These results confirm the usefulness of these tests according to previous studies of validation of each individual instrument [6,7,8,9,21,22,23,24,25,26,27,28]. However, interestingly, some tests achieved a greater diagnostic capacity than others.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results confirm the usefulness of these tests according to previous studies of validation of each individual instrument [6,7,8,9,21,22,23,24,25,26,27,28]. However, interestingly, some tests achieved a greater diagnostic capacity than others.…”
Section: Discussionsupporting
confidence: 88%
“…Items overlapping across the different cognitive tests (for instance, drawing a clock or specific questions regarding orientation) were only administered once. The following tests were carried out in their Spanish version: ACE-III [21,22,23], MIS [24], MMSE [25,26], MoCA [27], and RUDAS [28] (Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…Details regarding translation and validation of the ACE-III may be found in the validation study previously reported [4]. The test is available on the following website: www.neura.edu.au/frontier/research/test-downloads.…”
Section: Methodsmentioning
confidence: 99%
“…The third version of the ACE (ACE-III) has recently been developed and validated in English and Spanish [3,4]. Its specific characteristics, including five cognitive domains (attention, memory, fluency, language, and visuospatial skills) and a total score, and the correlation with standardized neuropsychological tests suggest that the ACE-III may be useful as a screening instrument and valuable as a short general neuropsychological battery [3].…”
Section: Introductionmentioning
confidence: 99%
“…Funcionamiento cognitivo: Se utilizó la versión en español del Addenbrooke's Cognitive Examination revisado (ACE-R) 35 . Es una prueba cognitiva breve que evalúa seis dominios cognitivos: orientación, atención, memoria, fluidez verbal, lenguaje y habilidades visoespaciales.…”
Section: Instrumentosunclassified